2019
DOI: 10.1097/01.nep.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Professional Value Development: Can We Do Better?

Abstract: AIM The purpose of this study was to identify whether differences exist in nursing professional values based on program type and/or geographic location. BACKGROUND Deliberate inclusion of values formation is critical to nursing education and high-quality nursing care. There is limited research comparing professional values development among students in all types of prelicensure RN programs and no research comparing students’ professional values between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…Our study showed that, in school A, subjects in the ABSN programme reported a higher level of professional value then subjects in the BSN programme. It was supported by literature (Feller et al., 2019 ). Contradictory result was found in school B.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our study showed that, in school A, subjects in the ABSN programme reported a higher level of professional value then subjects in the BSN programme. It was supported by literature (Feller et al., 2019 ). Contradictory result was found in school B.…”
Section: Discussionsupporting
confidence: 72%
“…In regard to the types of programmes, some studies found that the BSN students had higher professional values than the students with the associate degree in nursing (Fisher, 2014 ; Martin et al., 2003 ). Conversely, some studies showed that the BSN students reported less professional values than the students in the diploma and the ABSN programmes (Feller et al., 2019 ). There were also studies demonstrated no statistical difference was observed in the overall nursing values between the traditional and the accelerated graduating senior BSN students (Astorino, 2006 ), or among nursing students, new graduates and seasoned nursing profession (LeDuc & Kotzer, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies that were conducted in various countries have also found that nursing students give great importance to professional values. Mean NPVS-R score of Indonesian, Spanish, Colombian nursing students and different program types in USA were found as 95.80 (23), 109.82, 116.30 (24), and 113.23-102.96 (25), respectively. Appropriate development of professional values is an important educational goal.…”
Section: Discussionmentioning
confidence: 94%
“…Yapılan çalışmalarda simülasyon ve rol modeli üzerinden gerçekleştirilen hemşirelik eğitimlerinin öğrencilerin profesyonellik değerleri üzerinde olumlu etkilerinin olduğu belirlenmiştir. 15 Okulların müfredatları 16 , öğrencilerin sınıf seviyesi 5,14 , mesleki bir kuruluşa üye olmak 17 , kadın olmak 17…”
Section: öğRencilerin Tanıtıcı öZellikleriunclassified